Synthesis and Characterization of Certain New Azo Polyimides - RAJENDIRAN, T.V.; LAKSHMI, L. (Asian Journal of Chemistry, 2010)
Ten new aromatic-aliphatic polyimides containing azo linkage in the main chain, based on 3,3,'4,4'-azobenzene tetra carboxylic dianhydride and different aliphatic long chain diamines, were synthesized.The polymers were characterized by viscosity, solubility, spectroscopy, TGA and DTA.